Comparative studies on the effects of lincomycin and bacitracin on hematobiochemical and immunological parameters in broiler chickens - A. Elkomy, Ashraf; Farag, Enas; I. Elgharbawy, Elshahat; Elbadawy, Mohamed (International Journal of Pharmacology and Toxicology, 2019)
A total of 100 one-day-old healthy broiler chicks were used to study the effects of lincomycin and bacitracin on some hematobiochemical and immunological parameters. Chicks were divided into four equal groups, 25 each. The first group was kept as control; the 2nd group was received 0.5 g of lincomycin per liter; the 3rd group was received 100 mg bacitracin per liter and the 4th group was administered both lincomycin and bacitracin, each at the above-mentioned dose. Drugs were given in drinking water for 5 successive days from 20th to 25th day of age. Bodyweight was recorded at the beginning of the experiment and at 1st-day post administration where body performance was recorded. One day post administration, blood samples were collected for estimation of hematobiochemical and immunological alterations. The obtained results revealed that broiler chicks administered lincomycin or bacitracin or both revealed a marked increase in bodyweight, weight gain, phagocytic activity, phagocytic index, erythrocytic count, hemoglobin level, packed cell volume, total leukocytic count, serum total protein, albumin, total globulin, Î±, Î² and Î³ globulin. Furthermore, a significant elevation in malondialdehyde associated with a marked reduction in albumin-globulin ratio, serum total lipid, cholesterol and triglyceride and a significant decrease in catalase and superoxide dismutase, were recorded, compared with the control group. In conclusion, lincomycin and bacitracin either alone or in combination have positive impacts on growth performance, immunological and hematobiochemical parameters of broiler chickens. So, it is recommended to use both drugs as growth promoters in broiler chickens.Â Â Â